Centralized Regime Gaining Information Capacity: Can China Approach to Innovation Frontiers? - Feng, Kaidong; Jiang, Ziying (Journal of Contemporary China, 2024)
Why does the Chinese government have unsatisfactory policy performance in frontier innovation compared to its extraordinary achievements in the world factory model? Since the perspective of political system cannot provide an effective explanation, this article looks at this phenomenon from the viewpoint of information capacity. This article argues, the Chinese state has insufficient information capacity to promote frontier innovation—it has not developed an effective system to seize enough information through industrial practice to forge policies for frontier innovation. With the market-oriented reforms, the Chinese government has abandoned a top-down administrative coordinative system to organize science and technology (S&T) activities, and employed more market-oriented innovation policies. This article quantitatively assesses three main types of innovation policies, showing that the Chinese government has not achieved its expected goals of promoting frontier innovation. Interviews and long-term observations prove that the Chinese government lacks professional and penetrating capacities to seize and interpret information through industrial practice, and to effectively formulate and implement innovation policies—especially those aiming at frontier technologies with more complex information. This article sheds light on the relationship between the state and the market in the new era and state capacity building for technology and industrial policies.